Giants in the lab: Model conservation and the anaphoric progression of design - Yaneva, Albena (Journal of material culture, 2021)
How is an architectural model consolidated and re-assembled in conservation to be able to continue to communicate a design concept? How does the work of care and preservation of models reveal knowledge about the often taken-for-granted dynamics of creative processes? To provide answers, this article draws on Etienne Souriau’s philosophy of creativity and follows how the ‘modes of existence’ of creative works are re-enacted in the anaphoric progression of conservation. Basing her findings on ethnography at the Canadian Centre for Architecture, the author examines the epistemic complexity of specific situations of assessing, preserving and assembling large complex scale models. Unpacking the specificity of model conservation, it is argued, allows us to challenge two established beliefs on creativity: the myth of the stable ontology of historically valuable cultural objects and the myth of teleology of creative processes. Conservation-in-action demonstrates the subtle mechanics of crafting historiographic knowledge in the arts.